Comparison Of Post-Cesarean Section Pain Medication With Spinal Anesthesia Method Eracs And Without ERACS - Boyke Marthin Simbolon; Thoriq Akrom; Muhammad Chairul (Green Publisher Indonesia, 2024)
This study focused on the observation of pregnant women after surgery to determine the comparison of drugs and pain scales after surgery with the ERACS method and the method without ERACS. This study aims to determine the comparison of drugs and pain scales in patients after Sectio Caesarea surgery using the ERACS method and without ERACS. Currently, the Enhanced Recovery After Caesarian Surgery (ERACS) method as a perioperative program is popular, because it is considered to have a faster healing time and minimize pain so as to provide comfort to patients. This quantitative study was designed using a Cross-Sectional approach. The research sample was 40 respondents whose Pain Scale was measured using the Visual Analog Scale (VAS) measured with an observation sheet. Based on the results of statistical analysis. In the results of the Univariate test analysis on drug administration and pain scales of both VAS variables after (24 hours). It can be concluded that there is a difference between the amount of pain medication given and the pain scale with the ERACS method and the method without ERACS. The ERACS method has been shown to be more effective in reducing pain after Sectio Caesarea surgery and accelerating patient recovery compared to the method without ERACS. These findings support the use of the ERACS method as a standard of care to improve patient comfort and clinical efficiency